MLGSA: Multi-Leader Gravitational Search Algorithm for MultiObjective Optimization Problem - Mohd Riduwan, Ghazali; Khairul Hamimah, Abas; Badaruddin, Muhammad; Nor Azlina, Ab. Aziz; Kian, Sheng Lim (International Information Institute, 2017)
Recently, we have introduced Multi-Leader Particle Swarm Optimization (MLPSO) algorithm for multi-objective optimization problem. Better convergence and diversity have been observed over the conventional Multi-Objective Particle Swarm Optimization. In this paper, the same concept is extended to Gravitational Search Algorithm (GSA). The performance is investigated by solving a set of ZDT test problem. An analysis also is performed by varying the value of initial gravitational constant.